The unconstitutionality of state and municipal curfews (Research, Society and Development, 2022)
The present article does not intend to analyze the necessity or effectiveness of the measures restricting locomotion and social distancing as methods of confronting the COVID-19 pandemic, these aspects will not be analyzed. This article aims only to analyze the constitutional legal aspects of curfew, in view of its legal nature and its current application by the entities of the federation, such as states and municipalities. In this sense, the present text will be developed in a perspective of analysis of the application of the constitutional legal resource called "curfew", which has clearly predetermined rules of creation and application. Thus, a study will follow from a survey of literature where authors conceptualize and discuss the theme in question, bringing the historical path of curfew until its application today, emphasizing the aspects linked to fundamental rights as a vector to clarify the constitutionality of this instrument used as a means of containing the spread of coronavirus.